Radiation-induced angiosarcoma of the parotid gland after postoperative radiotherapy for hypopharyngeal carcinoma. Issue 6 (December 2019) - Arai, Akihito; Ozawa, Satomi; Kinoshita, Shota; Yoshimura, Kanako; Mitsuda, Junichi; Saburi, Sumiyo; Mori, Daichi; Takenaka, Mari; Tsujikawa, Takahiro; Konishi, Eiichi; Hirano, Shigeru
Abstract: Secondary carcinogenesis within the irradiation range is one of the most severe problems in cancer survivors. A 60-year-old woman developed hypopharyngeal carcinoma, and she received radical surgery and postoperative radiotherapy. Eight years later, brown pigmentation and induration were observed in the left subaural region. Fine-needle aspiration biopsy revealed malignancy and the parotid tumor was diagnosed as recurrence of hypopharyngeal carcinoma. Neoadjuvant chemotherapy followed by radical parotidectomy was performed. The pathological diagnosis was angiosarcoma, which was most likely induced by past irradiation. About two months after surgery, lung metastases were detected. Docetaxel did not affect to lung metastases, but paclitaxel therapy was partially effective. The lung tumors increased in size, and brain metastases developed, resulting in death. Both neoadjuvant chemotherapy and radical surgery played important roles in the local disease control. Administration of newer agents as adjuvant chemotherapeutic agent should also be considered for improving the prognosis.